Genetic variability, correlation and path coefficient analysis for yield and yield components in transplant aman rice (Oryza sativa L.) - Roy, Ripon Kumar; Majumder, Ratna Rani; Sultana, Shahanaz; Hoque, ME; Ali, MS (Bangladesh Journal of Botany, 2018)
Analysis of variance revealed significant differences among the genotypes for all the traits. Flag leaf area (0.643**), productive tillers per plant (0.450**), 1000-grain weight (0.785**) and harvest index (0.920**) showed positive and strong significant association with grain yield per plant at genotypic level whereas plant height (–0.418*) and per cent spikelet sterility (–0.489**) possessed significant negative correlation with grain yield per plant. Flag leaf area (0.157) productive tillers per plant (0.481), 1000-grain weight (0.228), growth duration (0.080) and harvest index (0.544) exhibited direct effect on grain yield. Considering the correlation and path analysis flag leaf area, productive tiller per plant, 1000-grain weight and harvest index are important characters to be considered for yield improvement.